(3TQM OjhGf GdCNWds - (3CHh eGdc ZjGK Hf ZhK HfWGQbI Hf YeQh GdJZdHj, GdGNWd,J (B90 (3g` s
(3ChdgG (B:s
(3GdegGOGg Cf jejd eQg jefg , heQg jSQg hbGd ZjQg fgGOjg Gi JQaYg bdjdkG s
(3BNQgG (B:s
(3WdbJehfG CfGSkG bGWYj bQf eSJVQHjf ceG jSJVQH GdjSQ s
(3CjVG GdOjhGf (B" (3JMJ Qbe (B877s
(3fSNI KGfjIs
(3bWYI ef TQM deLghds
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs